Exploring pharmacists’ orientation towards patients in Portuguese community pharmacies - Cavaco, Afonso Miguel (2020)
Background: Patient-centered care has been associated with improved patient outcomes and healthcare satisfaction. The present study aimed to explore pharmacy practitioners’ orientation to patients in daily work, as well as job satisfaction as a possible associated factor. Methods: A cross-sectional survey of a sample of Portuguese community pharmacists was used for gathering participants’ demographics, professional and work-related data, self-perceived level of technical and relational competencies, and the importance ascribed to these skills. The Portuguese version of the Patient-Practitioner Orientation Scale (PPOS) and a Portuguese-reduced version of a Healthcare Job Satisfaction Scale completed the online questionnaire. Results: A sample of 274 respondents comprised 81.1% females, with a mean age of 37.2 years, 11.6 years of work experience on average, and subject to a work intensity of 5.36 clients per hour, mainly for counter dispensing (73.0%). Overall, technical competencies were significantly more important than relational ones, but practitioners with fewer experiences self-perceived as weaker in communication competencies. Females scored higher in relational competencies importance as well as in PPOS (p < 0.05). No significant difference in PPOS was found between pharmacists with more and less direct interaction with patients, but higher when performing consultation services (p < 0.05). Conclusions: The existing orientation to patients seems to be under the desired levels and independent of community pharmacists’ work intensity, nevertheless linked with work experience and differentiated patient services. Although professionals might recognize the importance of relational competencies to provide patient-centered care and achieve better outcomes, it is essential to promote clinical training amongst community pharmacists.